2012
DOI: 10.1111/j.1540-8175.2012.01810.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Treatment Improves Myocardial and Peripheral Blood Flow in Familial Hypercholesterolemia Subjects without Evidence of Coronary Atherosclerosis

Abstract: Patients with FH and no obstructive CAD have blunted MBF reserve and lower FMD values as compared with healthy volunteers. Both FMD and MBF reserve were normalized after atorvastatin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…We found that early treatment with statins was associated with improved microcirculatory function, similar with the findings of previous studies (38,42,48). The mechanisms by which statins protect microcirculatroy function include their anti-inflammatory effect, endothelium protective effect, and antiremodeling effect on left ventricular (60)(61)(62)(63)(64).…”
Section: Discussionsupporting
confidence: 89%
“…We found that early treatment with statins was associated with improved microcirculatory function, similar with the findings of previous studies (38,42,48). The mechanisms by which statins protect microcirculatroy function include their anti-inflammatory effect, endothelium protective effect, and antiremodeling effect on left ventricular (60)(61)(62)(63)(64).…”
Section: Discussionsupporting
confidence: 89%
“…Three nonrandomized studies reported a significant within‐group effect of treatment with rosuvastatin in patients with hypertension, and of treatment with atorvastatin and simvastatin in patients with angina pectoris and no CAD, respectively . In the remaining 4 nonrandomized studies, no effect was found after treatment with either atorvastatin (3 studies) or simvastatin (1 study), in patients with CAD or hypercholesterolemia …”
Section: Resultsmentioning
confidence: 99%
“…Several studies showed that glycemic improvement normalizes microvascular function in diabetic patients 22,23 . Medications such as statins 24 or glucagon-like peptide-1 agonists 25 might improve microvascular function. Nicorandil moderately improved exercise-induced myocardial ischemia in microvascular angina patients by dilating both epicardial and resistance vessels and modulating the vasomotor responses of the vessels to sympathetic stimulation 26 .…”
Section: Discussionmentioning
confidence: 99%